A case of successful concurrent anti-cancer treatment in a patient who developed follicular lymphoma during treatment with afatinib for advanced lung adenocarcinoma. (2019) - Masuhiro, Kentaro; Koh, Genju; Takata, So; Nasu, Shingo; Takada, Hiromune; Morita, Satomu; Tanaka, Ayako; Shiroyama, Takayuki; Morishita, Naoko; Suzuki, Hidekazu; Okamoto, Norio; Kawasumi, Hiromi; et al.
Abstract: The present report describes the case of a 64-year-old woman with advanced lung adenocarcinoma expressing mutant epidermal growth factor receptor (EGFR). The patient developed follicular lymphoma during treatment with the EGFR-tyrosine kinase inhibitor afatinib. Standard immunochemotherapy for follicular lymphoma was introduced in addition to continuing treatment with afatinib for lung cancer. Immunochemotherapy was effective and improved the patient's performance status while afatinib controlled the progression of lung cancer. Our case study suggests that it is safe to introduce standard immunochemotherapy for patients who develop malignant lymphoma while continuing treatment with tyrosine kinase inhibitors for lung adenocarcinoma expressing mutant EGFR.